Reconstructing extrachromosomal DNA structural heterogeneity from long-read sequencing data using Decoil - Giurgiu, Mădălina; Wittstruck, Nadine; Rodriguez-Fos, Elias; Chamorro González, Rocío; Brückner, Lotte; Krienelke-Szymansky, Annabell; Helmsauer, Konstantin; Hartebrodt, Anne; Euskirchen, Philipp; Koche, Richard P.; Haase, Kerstin; Reinert, Knut; et al.

(untitled) (Genome Research, 2024)
Circular extrachromosomal DNA (ecDNA) is a form of oncogene amplification found across cancer types and associated with poor outcome in patients. ecDNA can be structurally complex and can contain rearranged DNA sequences derived from multiple chromosome locations. As the structure of ecDNA can impact oncogene regulation and may indicate mechanisms of its formation, disentangling it at high resolution from sequencing data is essential. Even though methods have been developed to identify and reconstruct ecDNA in cancer genome sequencing, it remains challenging to resolve complex ecDNA structures, in particular amplicons with shared genomic footprints. We here introduce Decoil, a computational method that combines a breakpoint-graph approach with LASSO regression to reconstruct complex ecDNA and deconvolve co-occurring ecDNA elements with overlapping genomic footprints from long-read nanopore sequencing. Decoil outperforms de novo assembly and alignment-based methods in simulated long-read sequencing data for both simple and complex ecDNAs. Applying Decoil on whole-genome sequencing data uncovered different ecDNA topologies and explored ecDNA structure heterogeneity in neuroblastoma tumors and cell lines, indicating that this method may improve ecDNA structural analyses in cancer.